Beyond bling voices of hip hop in art - McLendon, Matthew (Scala, 2011)
"These ten artists who have incorporated hip-hop/street culture into their oeuvre in provocative manners encourage us to question and expand our ideas of what it means to speak with a particularly urban voice in this time of advanced globalization and capitalism."--p.7